Treatment Of Palm Oil Mill Effluent From Polishing Pond Using Calcinated Limestone Roughing Filter - Dashti, Arezoo Fereidonian (2017)
Treatment of wastewater is one of the major problems faced by palm oil mill operators. One of the palm oil mill industries in Sungai Kecil Nibong Tebal, Pulau Pinang, Malaysia is experiencing a high concentration of turbidity, COD, colour, suspended solid and ammoniacal nitrogen in the final effluent after biological treatment that exceeds the standard discharge limit. The purpose of the present study is to investigate the suitability of using raw and calcinated limestone as low cost filter media for the treatment of treated effluent by using horizontal roughing filter. The physico-chemical treatment adopted in this study is preferred over other methods because of its simplicity, easy maintenance and quality control. The last treatment pond of palm oil mill effluent is the polishing pond where wastewater is directly discharged to the river. The polishing pond was selected for sampling in this study. The minimum and maximum concentrations of turbidity, COD, colour, suspended solid, and ammoniacal nitrogen in the polishing pond were 200 - 650 NTU, 2,200 – 3,300 mg/L, 3,000 – 5,000 PtCo, 400 - 730 mg/L, and 190 – 300 mg/L respectively. The parameters used in this study were particle sizes of limestone of 4, 12 and 20 mm, flowrates of 20 mL/min, 60 mL/min, and 100 mL/min and temperatures of 400 ˚C, 600 ˚C and 800 ˚C. Results indicated that a smaller particle size of limestone (4 mm) was more effective than a larger particle size of limestone (20 mm) because smaller sized particles of filter media have higher surface area which leads to high adsorption capacity. In contrast, a low flow rate (20mL/min) results in higher column saturation time, while higher flow rate results in shorter column saturation time and shows low removal efficiency. The study indicated that calcinated limestone at 800 ˚C has the highest removal efficiency for turbidity, COD, colour, SS and NH3-N (66%, 50%, 52%, 60% and 57% respectively) at smaller sized filter media (4 mm) and lower flow rate (20 mL/min) compared to calcinated limestone at different temperature and raw limestone. The batch results showed that the optimum dosage of calcinated limestone at 800 ˚C for removing turbidity, COD, colour, SS and NH3-N (69.23%, 48.23%, 40.13%, 70.81%, 50% respectively) was 85 g, whereas the optimum settling time was 5 hours. High removal efficiency was obtained in acidic phase for all parameters, but NH3-N was removed efficiently at pH 10 (58.17%) for calcinated limestone at 800 ˚C. The equilibrium adsorption data for turbidity, COD, colour, SS and NH3-N (0.959, 0.916, 0.935, 0.909, 0.977 respectively) was wellfitted with the Langmuir isotherm compared to that of Freundlich isotherm, indicated by high R2 value for small sized calcinated (800 ˚C) limestone.